2017
DOI: 10.7759/cureus.1080
|View full text |Cite
|
Sign up to set email alerts
|

Osborne’s Ligament: A Review of its History, Anatomy, and Surgical Importance

Abstract: When discussing the pathophysiology of ulnar neuropathy, Geoffrey Vaughan Osborne described a fibrous band that can be responsible for the symptoms seen in this disorder. In this paper, we take a glimpse at the life of Osborne and review the anatomy and surgical significance of Osborne’s ligament. This band of tissue connects the two heads of the flexor carpi ulnaris and thus forms the roof of the cubital tunnel. To our knowledge, no prior publication has reviewed the history of this ligament, and very few aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…Therefore, identifying the correlation between the tendinous structures of the medial elbow and the ulnar nerve is important. Previous anatomical studies have reported that the ulnar nerve traversed the upper arm from the anterior to the posterior compartment at the arcade of Struthers to enter the cubital tunnel, the floor of which consisted of the olecranon, medial joint capsule, posterior bundle of the UCL, and the transverse ligament (e.g., Cooper's ligament) (Morrey and An, ; Granger et al, ). Previous reports have also described that the compression of the ulnar nerve may occur at several sites along this path, such as Osborne's ligament (Bozentka, ; Granger et al, ), the brachial ligament (Wehrli and Oberlin, ), the anconeus epitrochlearis (Grewal et al, ), and the subanconeus muscle, of which the highest concentration of fibers was in the joint capsule near the groove of the ulnar nerve (Tubbs et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, identifying the correlation between the tendinous structures of the medial elbow and the ulnar nerve is important. Previous anatomical studies have reported that the ulnar nerve traversed the upper arm from the anterior to the posterior compartment at the arcade of Struthers to enter the cubital tunnel, the floor of which consisted of the olecranon, medial joint capsule, posterior bundle of the UCL, and the transverse ligament (e.g., Cooper's ligament) (Morrey and An, ; Granger et al, ). Previous reports have also described that the compression of the ulnar nerve may occur at several sites along this path, such as Osborne's ligament (Bozentka, ; Granger et al, ), the brachial ligament (Wehrli and Oberlin, ), the anconeus epitrochlearis (Grewal et al, ), and the subanconeus muscle, of which the highest concentration of fibers was in the joint capsule near the groove of the ulnar nerve (Tubbs et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…This construction of the cubital tunnel roof has been classified as a type II cubital tunnel retinaculum (O'Driscoll et al, ). In individuals with no anconeus epitrochlearis, the roof of the cubital tunnel is composed of Osborne's ligament, also known as the arcuate ligament or tendinous arch (Granger et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…2c). 7 In some patients, the ceiling is replaced by the aconeus epitrochearlis muscle, thought to be an accessory cause of ulnar nerve compression in some patients. 4 The tunnel floor is made up of the medial collateral ligament (MCL) and elbow joint capsule, while the medial epicondyle and olecranon act as the walls on either side.…”
Section: Anatomymentioning
confidence: 99%
“…4,6 Patients may notice point tenderness and pain overlying the nerve at the medial aspect of the elbow due to inflammation. As elbow flexion compresses the area of the cubital tunnel and pinches the nerve, 1,2,7,11,12 paresthesias are often exacerbated by elbow flexion activities such as phone use or athletic activities that require repetitive elbow motion. Night symptoms severe enough to cause awakening are a common complaint as many people sleep with the elbow in a flexed position.…”
Section: Clinical Presentationmentioning
confidence: 99%